International trade in services : firm-level evidence for Portugal - Amador, João (2020)
This paper adds to the existing firm-level evidence on international trade in non- tourism services, using a new Portuguese database merged with balance-sheet data. In accordance with the literature, we find that a small number of firms that both export and import services (two-way traders) with diversified service and geographi- cal portfolios account for a substantial share of trade flows. Compared with one-way traders, two-way traders are larger, older, more productive, more profitable and have a higher share of foreign equity. Considering all margins of firm-level trade and con- trolling for firms’ characteristics, the intensive margins of exports and imports of services are positively related to both productivity and profitability. Regarding the extensive margins, the number of services imported is also positively associated with firms’ performance.